2016
DOI: 10.1088/1741-2560/13/2/026013
|View full text |Cite
|
Sign up to set email alerts
|

A robust adaptive denoising framework for real-time artifact removal in scalp EEG measurements

Abstract: The proposed method allows real-time adaptive artifact removal for EEG-based closed-loop BMI applications and mobile EEG studies in general, thereby increasing the range of tasks that can be studied in action and context while reducing the need for discarding data due to artifacts. Significant increase in decoding performances also justify the effectiveness of the method to be used in real-time closed-loop BMI applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
101
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(109 citation statements)
references
References 20 publications
0
101
0
3
Order By: Relevance
“…This filter significantly increased decoding accuracy of user intentions using EEG to control a lower-body exoskeleton, as it was shown in (Kilicarslan et al, 2016). A previous study showed that quality of EEG signals (i.e., signal to noise ratio, standard deviation) affect decoding accuracies of treadmill walking (Luu et al, 2015), which was the case in this research.…”
Section: Discussionmentioning
confidence: 69%
“…This filter significantly increased decoding accuracy of user intentions using EEG to control a lower-body exoskeleton, as it was shown in (Kilicarslan et al, 2016). A previous study showed that quality of EEG signals (i.e., signal to noise ratio, standard deviation) affect decoding accuracies of treadmill walking (Luu et al, 2015), which was the case in this research.…”
Section: Discussionmentioning
confidence: 69%
“…In the case of a disagreement, a third reviewer (TPL) was decisive. Two additional publications that do not contain all the keywords in their titles were manually identified as relevant studies (Kilicarslan et al 2016.…”
Section: Search Methods For Identification Of Studiesmentioning
confidence: 99%
“…With little risk of falls, Lokomat provides a safe testing environment. The Rex exoskeleton keeps its balance without the support of crutches or any other external system, although in practice, human spotters are often required to guarantee safety (Kwak et al 2015, Kilicarslan et al 2016. The customized exoskeleton used in Donati et al (2016) is also reported to be stable in single support stance without the need of crutches as well.…”
Section: User and Robot Typesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, most components of electrooculogram (EOG) as well as the low-frequency drifts and bias exerted few effects on this study [23, 24]. In addition, for artifacts with a frequency higher than 4Hz, we applied a statistic regarding its duration percentage to the series duration.…”
Section: Methodsmentioning
confidence: 99%